O Imposto Territorial Rural (ITR) como fonte de receita municipal - Rodrigues, Franco Coelho (2012)
The Federal Government, giving efficacy to section III of § 4 of art. 153 of the Federal Constitution enacted Law No. 11,250, of december 27, 2005, which provides that the Union, through an agreement, delegate responsibility for monitoring and collection for the Municipalities and the Federal District on the Rural Land Tax (ITR). By adhering to the agreement, the cities appropriated the entire revenue of ITR, paying, however, with the cost of administering them. Without membership, municipalities receive the transfer equivalent to 50% of the proceeds. This study aims to evaluate the potential of revenue collection ITR considering various scenarios of tax administration costs, serving as a resource for decision-making of the city manager about the adherence agreement with the Union For this, we used data agricultural census 2006 for 184 municipalities in the Ceará linear regression model of OLS. As a result, it was found that characteristics such as the Gini index, the total area of establishments (crop, pasture, woods and forests, agroforestry and so residual) value of goods and livestock area of influence on the collection of ITR. It is presented as a consequence, the potential revenue collection of the tax to municipalities on the basis of the Ceará cost scenarios considered.